Targeted Protein Degradation by Chimeric Small Molecules, PROTACs and SNIPERs - Naito, Mikihiko; Ohoka, Nobumichi; Shibata, Norihito; Tsukumo, Yoshinori (Frontiers in Chemistry, 2019)
Technologies that induce targeted protein degradation by small molecules have been developed recently. Chimeric small molecules such as Proteolysis Targeting Chimeras (PROTACs) and Specific and Nongenetic IAP-dependent Protein Erasers (SNIPERs), and E3 modulators such as thalidomides, hijack the cellular machinery for ubiquitylation, and the ubiquitylated proteins are subjected to proteasomal degradation. This has motivated drug development in industry and academia because “undruggable targets” can now be degraded by targeted protein degradation.